INFLUENCE OF PARENTAL INCOME AND ENCOURAGEMENT ON ACADEMIC SELF-EFFICACY AND ACHIEVEMENT AMONG MALAYSIAN UNIVERSITY STUDENTS - Yee Kee Tan; Mimi Fitriana; Ching Sin Siau; Vimala Govindasamy; Meng Chuan Ho, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Parents play an important role in shaping the academic achievement of their children. This study aimed to investigate the association between parental factors and university students’ academic self-efficacy and academic achievement, and the correlation between academic self-efficacy and the academic achievement of university students within the context of Malaysia. The cross-sectional study recruited participants using an online questionnaire, which included demographic information such as age, current education status, current working status, Cumulative Grade Point Average (CGPA) and parents’ monthly income, the Parental Encouragement Scale (PES), and Academic Self-efficacy (ASE) Scale. A total of 196 participants responded to the survey. The results of the Pearson’s correlation showed that parental encouragement was positively correlated with academic self-efficacy (r (196)=.144, p=.044), whilst academic self-efficacy was positively correlated with CGPA (r (196) = .241, p=.001). The multiple linear regression model showed that part-time working status (β=-.184, p=.008) and academic self-efficacy (β=.252, p<.001) were significantly associated with CGPA. Parents should be encouraged and trained to develop academic self-efficacy in their children.